Les seigneuresses de l'île - Barthe, Marcel (Les Argoulets, 2024)
Keywords: Congrégation de Notre-Dame; Femmes; Île-des-Soeurs

« Il s'en tuë jusques dans les jardins de Québec ». La place des animaux sauvages dans la ville (Québec et Montréal, 1663-1763) - Riguelle, William (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Alimentation; Faune

Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Quand l'art prend la rue - Bilodeau, Maxime (Continuité, 2024)
Keywords: Monuments; Places publiques

Le fort de Verdun localisé - Dubeau, Pierre (Les Argoulets, 2024)
Keywords: Forts; Verdun

L'émergence et la transformation des interfaces ville-industrie: Le cas de la planification urbaine d'Assomption Sud-Longue-Pointe à Montréal - Lambert, Olivier (Université du Québec à Montréal, 2024)
Keywords: Longue-Pointe

Passé et avenir d'une rivière montréalaise - Legault, Louise (Histoire Québec, 2024)
Keywords: Lachine; Lachine (canal); Pollution; Égouts

The High Ground: Mansions, Mythology, and the Mountain - Macleod, Roderick (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Paysages; Quartiers

La vie de John Elsdale Molson - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Rosemont

La rue Saint-Denis (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Cherrier, Côme-Séraphin; Hôpital Sainte-Justine; Levasseur, Irma; Massicotte, Édouard-Zotique; Patrimoine; Plateau Mont-Royal (arrondissement); Saint-Denis (rue)

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

L’ancien cimetière Saint-Antoine (1799-1854) et son voisin rural à Pointe-aux-Trembles (1709-1843) : analyse comparative de la mortalité des enfants de deux populations du XIXe siècle sur l’île de Montréal - Duchemin, Emmanuelle (Université de Montréal, 2023)
Keywords: Enfants; Mortalité; Pointe-aux-Trembles; Saint-Antoine

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

Liens d’amitié, de parenté et d’appartenance à une collectivité : genre, itinérance et aide mutuelle à Montréal au début du XIXe siècle - Poutanen, Mary Anne (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Itinérance

Le mystère urbain de Crawford Park. Des origines à la Dépression- (Partie 1) - Voisine, John (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Quartiers; Verdun

L'Hôtel de ville a 130 ans. La fabuleuse histoire de la mairie d'Outremont - Waché, Gabriel; Bizier, Hélène-Andrée (Mémoire vivante, 2023)
Keywords: Hôtel de ville; Outremont; Patrimoine

Une mesure d'origine britannique. Les barrières à péage à Outremont - Waché, Gabriel; Bizier, Hélène-Andrée (Mémoire vivante, 2023)
Keywords: Outremont; Routes

Les débuts de la poste à Ahunstic-Cartierville - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Bordeaux; Cartierville; Poste; Sault-au-Récollet

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

At St Anne's Market (1834-1844). All Kinds of Products, All Kinds of Meetings - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

St Anne's Market. A Long-Awaited Project - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Marchés; Sainte-Anne (marché)

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise; Cecchini, Lisa; Hamilton, Patricia; Knowles, Terry (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

For Our Collective Heritage. Nothing Is Loss Forever - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

A Building Transformed. From Market to Parliament - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Marchés; Parlement; Sainte-Anne (marché)

Discovering Parliament in Montréal - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Behind Strong Palings: Producing Knowledge in the Modern City at Montreal’s Emigrant Sheds, 1832-1852 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Choléra; Épidémies

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Aux origines du village de Saint-Jean-Baptiste, 1850-1861 - Robert, Jean-Claude (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

The Goode House (The Westmount Historian, 2021)
Keywords: Conservation; Famille; Jardins; Patrimoine

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Quand le temps s'arrête: une promenade dans le jardin de la maison Goode / Window to the Past: A Walk in the Garden of the Goode House - Adib, Danièle; Crépeau, Antoine (The Westmount Historian, 2021)
Keywords: Jardins

L'homme aux 300 clochers - Anctil, Gabrielle (Continuité, 2021)
Keywords: Bourgeau, Victor; Églises

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Au marché Sainte-Anne (1834-1844). Produits... et réunions de toutes sortes - Burgess, Joanne (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

Le marché Sainte-Anne. Un projet depuis longtemps souhaité - Burgess, Joanne (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

The Goode House: A Special Place - Cameron, Christina (The Westmount Historian, 2021)
Keywords: Conservation; Patrimoine

Le marché Sainte-Anne et ses eaux souterraines. Imaginer et construire de façon innovatrice - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

Pour la mémoire collective. Rien n'est jamais perdu - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

Au croisement de la perte de mémoire et de la créativité communautaire: de nouvelles innovations dans les anciens ateliers ferroviaires de Pointe-Saint-Charles - Elliott, Andrew (Bulletin de l'AQPI, 2021)
Keywords: Canadien National; Chemins de fer; Conservation; Grand Tronc; Patrimoine

Les paysages urbains historiques des canaux de Lachine et de Chambly: une démarche exploratoire. - Gelly, Alain; Paradis, Mathieu (Paysages du mouvement/paysages en mouvements: Trajectoires, perspectives et panoramas, 2021)
Keywords: Lachine (canal)

À la découverte du parlement de Montréal - Gignac, François (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Parlement

La transformation d'un bâtiment. De marché à parlement - Gignac, François (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Parlement; Sainte-Anne (marché)

À l'ombre de la montagne : le paysage archéologique du versant nord du mont Royal, Montréal, 1698-1900 - Janssen, Valérie (Université de Montréal, 2021)
Keywords: Cimetières; Mont-Royal (parc)

Un monument précurseur dans la définition d’une nouvelle identité architecturale dans le diocèse catholique romain de Montréal - Noppen, Luc (Journal of the Society for the Study of Architecture in Canada / Le journal de la Société d'étude pour l'architecture au Canada, 2021)
Keywords: Bourgeau, Victor; Sainte-Brigide (paroisse); Églises

Urban Picturesque. John James Browne and the Fire Stations of Montréal - Osborne, John (Journal of the Society for the Study of Architecture in Canada / Le journal de la Société d'étude pour l'architecture au Canada, 2021)
Keywords: Casernes; Pompiers

Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

Une histoire sociale de la prostitution: Montréal, 1800-1850 - Poutanen, Mary Anne (Les éditions du remue-ménage, 2021)
Keywords: Femmes; Prostitution

Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Keywords: Métropole; Port

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

1844-1849. Montréal, nouveau siège du gouvernement - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

De part et d'autre de la Petite rivière. Montréal naît et grandit - Stewart, Alan (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Faubourgs; Fortifications; Forts

On Both Shores of the Little River. Montréal Emerges and Evolves - Stewart, Alan (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Keywords: Faubourgs; Fortifications; Forts

Synagogue Architecture in Canada: A Summary History - Stiefel, Barry L. (Journal of the Society for the Study of Architecture in Canada, 2021)
Keywords: Juifs

Square Saint-Louis: Lieu mythique (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
Keywords: Librairie; Miron, Gaston; Monuments; Nelligan, Émile; Places publiques; Poésie; Squares; École littéraire de Montréal; Écrivains

La mutation vers un espace urbain moderne. Le projet de démantèlement des fortifications de Montréal - Beauchamp-Monfette, Joel (Cap-aux-Diamants, 2020)
Keywords: Fortifications

Cohabitation, exploitation et nuisances à Montréal et à La Nouvelle-Orléans : les relations entre les populations urbaines et animales, 1840-1890 - Gagnon, Benjamin (Université du Québec à Trois-Rivières, 2020)
Keywords: Alimentation; Faune

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

Du couvent des Dames du Sacré-Cœur à l’école secondaire Sophie-Barat. État des lieux d’une institution pionnière - M. Sénécal, Geneviève (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Keywords: Communautés religieuses

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Keywords: Lachine (canal); Paysages

La maison Nivard-De-Saint-Dizier au temps de John Crawford, haut lieu de chasse à courre - Tremblay Lamarche, Alex (Cap-aux-Diamants, 2020)
Keywords: Chasse à courre; Clubs; Crawford, John; Montreal Hunt Club; Nivard-De-Saint-Dizier (maison); Verdun